2016
DOI: 10.1186/s12906-016-1316-5
|View full text |Cite
|
Sign up to set email alerts
|

Liquid and vapour-phase antifungal activities of essential oils against Candida albicans and non-albicans Candida

Abstract: BackgroundThe management of Candida infections faces many problems, such as a limited number of antifungal drugs, toxicity, resistance of Candida to commonly antifungal drugs, relapse of Candida infections, and the high cost of antifungal drugs. Though azole antifungal agents and derivatives continue to dominate as drugs of choice against Candida infections, there are many available data referring to the anticandidal activity of essential oils. Since we have previous observed a good antimicrobial activity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…We demonstrated that the chemically diverse EOCs carvacrol, citral, trans‐cinnamaldehyde and linalool, and EOs rich in these EOCs, exhibit vapour‐phase‐mediated antimicrobial activity against both Candida species tested. Direct vapour‐phase antimicrobial activities were shown before for citral‐, carvacrol‐ and linalool‐rich EOs and their corresponding EOCs using different assays . Taking the variability of EO composition into account, this demonstrates that there is a degree of overlap between the direct vapour‐phase antimicrobial activity and the vapour‐phase‐mediated antimicrobial activity measured here.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…We demonstrated that the chemically diverse EOCs carvacrol, citral, trans‐cinnamaldehyde and linalool, and EOs rich in these EOCs, exhibit vapour‐phase‐mediated antimicrobial activity against both Candida species tested. Direct vapour‐phase antimicrobial activities were shown before for citral‐, carvacrol‐ and linalool‐rich EOs and their corresponding EOCs using different assays . Taking the variability of EO composition into account, this demonstrates that there is a degree of overlap between the direct vapour‐phase antimicrobial activity and the vapour‐phase‐mediated antimicrobial activity measured here.…”
Section: Resultssupporting
confidence: 65%
“…Direct vapour-phase antimicrobial activities were shown before for citral-, carvacrol-and linalool-rich EOs and their corresponding EOCs using different assays. 21,23,24 Taking the variability of EO composition 25,26 into account, this demonstrates that there is a degree of overlap between the direct vapour-phase antimicrobial activity and the vapour-phase-mediated antimicrobial activity measured here. Moreover, it indicates that reliable results can be obtained using the assay that we introduced.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In opposite, VPT detect the effect of gaseous phase produced by EO vapor and they can be easily combined with other techniques [8]. It should be highlighted that VPT can also be adapted to other different pathogens such as fungi and viruses [15][16][17][18]. According to the result of the microbiological assays, cinnamon bark, clove, thyme, peppermint, and citronella oils showed the most potent activity in both vapor and liquid systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thymus vulgaris Candida albicans [72,86,94,99,100] Thymus vulgaris Aspergillus flavus [92] Thymus vulgaris Aspergillus ochraceus [96] Thymus eriocalyx Thymus x-porlock Aspergillus niger [98] Thymus vulgaris Penicillium chrysogenum [96] Thymus serpyllum Dermatophytes [101] Thymus schimperi Penicillium chrysogenum [66] Thymus schimperi Verticillium sp. [66] Thymus schimperi Aspergillus tubingensis [66] Thymus schimperi Aspergillus minutus [66] Thymus schimperi Beauveria bassiana [66] Thymus schimperi Microsporum gypseum [66] deformation, deterioration, collapse, and of the conidia and/or hyphae [96].…”
Section: Thymus Plant Inhibited Microorganisms Referencesmentioning
confidence: 99%